Performance of a coupled level-set and volume-of-fluid method combined with free surface turbulence damping boundary condition for simulating wave breaking in OpenFOAM - Chatzimarkou, Eirinaios; Michailides, Constantine; Onoufriou, Toula (My University, 2022)
In the present study, an extension of the volume-of-fluid (VOF) method used in the open-source computational fluid dynamics (CFD) software OpenFOAM was developed, taking the advantages of the VOF and the level-set (LS) methods with an additional free surface turbulence damping (FSTD) boundary condition to restrict the overprediction of turbulence near the free surface. The coupled level-set and volume-of-fluid (CLSVOF) method has been developed, scripted, validated and proposed. The free surface elevation with the proposed CLSVOF method was validated in a developed numerical wave tank (NWT) against turbulence models used so far in OpenFOAM. Further, the validity of the present numerical model was evaluated for the case of plunging breaking waves against relevant experimental and numerical data. The outcome of this study demonstrates that the performance of the wave generation is improved with the proposed numerical model compared to existing turbulence models in OpenFOAM, creating a useful simulation add-on that generates long-term waves without unphysical dissipation, wave damping, and wave decay. The overprediction of turbulence created due to the significant difference in the fluid's density close to the free surface is limited by applying the FSTD boundary condition leading to a better representation of the flow field.
Keywords: Coupled level-set method; Volume-of-fluid method; Computational fluid dynamics; OpenFOAM; Free surface turbulence damping; Breaking waves